First aid manual the authorised manual of St. John Ambulance, St. Andrew's First Aid and the British Red Cross (Dorling Kindersley, 2011)
'First Aid Manual' covers all aspects of first aid, from emergency first aid and first aid for babies and children, to resuscitation. Find out how to treat over 100 different conditions, from splinters and sprained ankles, to strokes and unconsciousness and how to use essential equipment